The use of regenerative technologies for treatment of delayed fracture union in patient with menopausal osteoporosis - Maslennikov, Serhii; Kozhemyaka, Maksym; Golovakha, Maksym (Menopause Review/Przegląd Menopauzalny, 2025)
Delayed fracture union is a common complication in orthopedic practice, particularly in patients with osteoporosis. Advances in regenerative medicine, including mesenchymal stem cells (MSCs) within the stromal-vascular fraction, have introduced novel therapeutic approaches to address this challenge. This case describes a patient with postmenopausal osteoporosis and a congenital anomaly of the left lower limb who sustained a proximal tibial fracture with fragment displacement. Osteoporosis therapy was initiated, and the fracture was managed using external fixation and compression. Despite an improvement in bone mineral density over an eight-month period, radiographic assessment revealed no evidence of fracture union. Consequently, local administration of MSCs combined with needling at the fracture site was performed, followed by a series of autologous concentrated plasma (ACP) injections. Within three months, radiographic signs of bone callus formation were observed, ultimately leading to complete fracture union six months after the initiation of regenerative therapy. Although the limited number of cases in our clinic prevents definitive conclusions regarding the primary contributing factor in fracture healing, existing literature suggests that the mobilization of endogenous resources at the fracture site in high concentrations promotes tissue regeneration. This process is further facilitated by physical activity and adjunctive pharmacological treatment. Regenerative therapy integrating MSCs and ACP-derived growth factors represents a promising adjunctive approach for managing fracture complications in patients with systemic osteoporosis. This strategy has the potential to enhance bone healing while potentially delaying or even avoiding the need for more invasive surgical interventions.